Figurative Meaning in “Lang Leav” Poetry: Array - Azti, Tengku Mutiara; sari, Maya; Anayati, Wan (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2021)
This study concerns with the descriptive analysis of Figurative Meaning In “Lang Leav” Poetry. The problem of the study is (1) What are the types of figurative meaning used in Lang Leav poetry? (2) What is the dominant type of figurative meaning used in Lang Leav poetry? (3) Why was the type most dominantly used? The objective of the study is to find out the types of figurative meaning that is used in Lang Leav Poetry and to know the dominant types of figurative meaning that is used in Lang Leav Poetry and the reason why was the type most dominantly used. This study used a Keraf’s (2009) theory. The research method used is descriptive qualitative method to classify and analyze the poetry. The data sources are found to originate from Lang Leav poetry. The total number of the types of figurative meaning in Lang Leav poetry: personification is 2 (6%), hyperbole is 14 (45%), metaphor is 3 (10%), symbol is 3 (10%), simile is 4 (13%) and irony is 5 (16%). Hyperbole is the most dominant types because it indicated activities that happen in Lang Leav poetry. Hyperbole as the dominant types of figurative meaning in poetry because there are so many expressions are over expressed.